Effectiveness and Adverse Effects of Over-the-Counter Whitening Products on Dental Tissues - de Freitas, Maiara Rodrigues; de Carvalho, Marynara Mathias; Liporoni, Priscila Christiane Suzy; Fort, Ana Clara Borges; Moura, Rodrigo de Morais e; Zanatta, Rayssa Ferreira (Frontiers in Dental Medicine, 2021)
The role of bleaching agents (e.g., hydrogen peroxide) in tooth bleaching is quite well-described in a few literature studies and considered as the option choice for those desiring brighter teeth, but alternative methods have emerged to fulfill the desire of patients in a faster, easier, and cheaper way. In this context, whitening over-the-counter (OTC) products are available in several vehicles, such as toothpaste, rinses, gums, paint-on varnishes, and strips, but their effectiveness in terms of bleaching is questioned. This review aimed to describe their mode of action, whitening effectiveness, and harmful effects associated with the indiscriminate use of these products. Dentifrices usually present a combination of abrasives that can induce damage to the tooth surface without evidence of promoting real bleaching. The same was found for rinses, which might present a low pH, with an erosive potential. Charcoal has been included in the composition of these products to improve their whitening effect but there is no evidence supporting it. Regarding strips, they present hydrogen peroxide in a variety of concentrations and are the only OTC products able to promote bleaching. Despite the vehicle, an indication for the use of these products should be made after a careful individual diagnosis of the etiology of the dental staining, considering that most of them seem to be effective only in removing extrinsic stains or preventing their formation over enamel. Also, their indiscriminate use might induce damage and deleterious effects over tooth tissues or gingival tissues. The dentist should be aware of the composition and mode of action of each individual product as they change according to the composition and the vehicle used to recommend the best mode of usage. Still, there is no sound evidence that any of the described OTC products promote a better bleaching effect than the products indicated for a professional.